Single mothers, social capital, and work-family conflict - Teresa Ciabattari (W.E. Upjohn Institute for Employment Research, 2005)
The purpose of this paper is to examine work-family conflict among low-income, unmarried mothers. I examine how social capital affects work-family conflict and how both social capital and work-family conflict affect employment. I analyze the Fragile Families and Child Wellbeing Study, a national sample of non-marital births collected in 1998-2000 and 1999-2002. Results show that social capital reduces unmarried mothers' reports of work-family conflict, especially for low-income women. In addition, mothers who report high levels of work-family conflict are less likely to be employed; this pattern holds for women who are not looking for work as well as those who are. However, even at high levels of conflict, low-income women are more likely to be employed. The results suggest that work-family conflict has two consequences for unmarried women: it keeps them out of the labor force and makes it more difficult for women who want to work to maintain employment stability.
Keywords: 330; Alleinerziehende; Social Capital; Niedrigeinkommen; Erwerbstätigkeit; USA